How Loose, How Tight? : A Measure of Monetary and Fiscal Stance for the Euro Area - Batini, Nicoletta; Cantelmo, Alessandro; Melina, Giovanni; Villa, Stefania (Washington, D.C. : International Monetary Fund, 2020)
This paper builds a model-based dynamic monetary and fiscal conditions index (DMFCI) and uses it to examine the evolution of the joint stance of monetary and fiscal policies in the euro area (EA) and in its three largest member countries over the period 2007-2018. The index is based on the relative impacts of monetary and fiscal policy on demand using actual and simulated data from rich estimated models featuring also financial intermediaries and long-term government debt. The analysis highlights a short-lived fiscal expansion in the aftermath of the Global Financial Crisis, followed by a quick tightening, with monetary policy left to be the 'only game in town' after 2013. Individual countries' DMFCIs show that national policy stances did not always mirror the evolution of the aggregate stance at the EA level, due to heterogeneity in the fiscal stance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet